Empirical Analysis of the Emerging Trends in the Photovoltaic Technologies of Condensed Matter Physics - Deshpande, Neeta; Sharma, Santosh Kumar; William, P.; Pawar, A. B. (Journal of Nano- and Electronic Physics, 2023)
We examine some current developments in a subject that is developing at the intersection of conventional inorganic and organic materials. Inorganic and organic structural components co-exist in crystalline systems that make up hybrid inorganic-organic framework materials. Porous hybrid frameworks have established a lot of concentration in this field during the last several years because of their potential use in catalysis, separations, and sensors. Our study primarily focuses on the magnetic, optical, electrical, and dielectric characteristics that are normally the preview of condensed matter physics. The value of empirical research in understanding the processes of social, economic, and technological development cannot be overstated. In recent years, there has also been an increase in the deposition of thin films of hybrid compounds onto solid surfaces for possible use in surface chemistry and physics. The development of new technologies, like quantum computing and spintronic, and the understanding of how matter behaves under extreme situations, we demonstrate that these materials display a great variety of behavior in these domains and provide several fascinating prospects to the physics community. We also provide a brief overview of several of the characteristics of porous materials in terms of nano technology with hybrid approach. The field of hybrid technology still has a critical need for theory and simulation.